THE INFLUENCE OF TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP ON PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE IN EMPLOYEES OF PT MOYA KASRI WIRA JATIM - Nur Wakhidatul Fikriyah Salsabila; Khotim Fadhli (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to explore the impact of transformational and transactional leadership on employee performance, using job satisfaction as a mediating factor at PT Moya Kasri Wira Jatim. Methods: The study employes a quantitative metodology, using Partial Least Square–Structural Equation Modeling (PLS-SEM) for data analysis. The research involved a sample of 117 participants.Results: Results from the research show that transformational leadership enhances employee satisfaction (t= 6. 677; p < 0. 05). The mediation analysis demonstrates that job satisfaction does not act as a mediator between transformational and transactional leadership concerning performance (p > 0. 05).Conclusion and suggestion: From these observations, it can be deduced that enhancing employee performance is more closely related to the type of leadership exhibited style than by the level of job satisfaction directly. Therefore, companies need to optimize both leadership styles in a balanced manner to achieve maximum performance results. Keywords: Employee Performance. Job Satisfaction, Transformational Leadership, Transactional Leadership